2015
DOI: 10.1021/acs.langmuir.5b01184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water on Solvation Layers of Imidazolium-Type Room Temperature Ionic Liquids on Silica and Mica

Abstract: Effects of the addition of water on solvation layers of imidazolium-type room temperature ionic liquids (RT-ILs) have been studied through force curve measurements of atomic force microscopy (AFM). Two kinds of RT-ILs were employed in this study; one is a hydrophilic RT-IL (1-butyl-3-methylimidazolium tetrafluoroborate, BmimBF4), and the other is a hydrophobic one (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, EmimTFSI). These RT-ILs form solvation layers on hydrophilic solid substances (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 31 publications
(60 reference statements)
13
60
0
Order By: Relevance
“…Multiple repulsive layers were observed in the [EMIM][DCN] solution. This phenomenon is often observed in fluorine‐based RTILs . Figure shows the force curve profile of the [EMIM][DCN] solution.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Multiple repulsive layers were observed in the [EMIM][DCN] solution. This phenomenon is often observed in fluorine‐based RTILs . Figure shows the force curve profile of the [EMIM][DCN] solution.…”
Section: Resultsmentioning
confidence: 79%
“…The thickness of the repulsive layer closest to the solid surface (the first layer) was approximately 0.73 nm (Figure (1)), almost equal to the size of an [EMIM] cation (ionic radius = 0.32 nm) and a [DCN] anion (ionic radius = 0.33 nm) . This layer was considered cation‐rich because mica exhibited a negative potential . The width of the second repulsive layer was approximately 0.74 nm (Figure (2)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35] In addition, it was reported that water molecules could adsorb on silica surface in an ionic liquid by hydrogen bonding. 36 In the same manner, it was considered that ethanol could adsorb on the surface of silica nanoparticles via hydrogen bonds in an ionic liquid. As the result of ethanol adsorption, the formation of hydrogen bonds between the silica nanoparticles could be inhibited.…”
Section: Silica-nanoparticle-based μ-Dn Ion Gelmentioning
confidence: 99%
“…In addition, emission of HF gas derived from hydrolysis is a concern [36, [44][45][46]. Deterioration of the friction properties and disappearance of the adsorption layer have been reported in other ionic liquids when mixed with water [47][48][49]. However, both negative and positive effects were observed.…”
Section: Introductionmentioning
confidence: 99%